Fast and Accurate Calculation Techniques to Support Mathematics Learning of Elementary School Teachers in Takalar Regency: Teknik Berhitung Cepat dan Tepat Sebagai Penunjang Pembelajaran Matematika Guru-Guru Sekolah Dasar Di Kabupaten Takalar - Rusli, R.; Tahmir, Suradi; Arwadi, Fajar; Hastuty, H. (Yayasan Ahmar Cendekia Indonesia, 2020)
The application of fast calculation techniques in supporting the learning mathematics in this training activity aimed to increase the understanding of elementary school mathematics teachers about the fast calculation method that can be applied in basic algebraic calculation. The implementation of this activity was expected to improve the quality of Elementary School Mathematics education in Takalar Regency. This training used demonstration and question-and-answer methods about the fast calculation technique performed by elementary school teachers in Takalar Regency. The implementation of this activity began with observations and interviews with the Head of the Teacher and Education Personnel Division at the Takalar Regency Education Office. This activity was carried out by Syncronouse Online using the Zoom meeting application due to the Covid-19 Pandemic. There were 33 participants who attended the training. Based on the results of a questionnaire on the teacher’s perceptions about the use of fast calculation techniques, all teachers find this technique helpful. Therefore, the teachers will use this technique in teaching arithmetic to their students. Abstrak Penerapan teknik berhitung cepat sebagai penunjang pembelajaran Matematika dalam Kegiatan pelatihan ini bertujuan untuk meningkatkan pemahaman guru- guru matematika sekolah dasar akan sebuah metode berhitung cepat yang dapat diterapkan dalam operasi dasar berhitung aljabar. Target khusus yang ingin dicapai dalam kegiatan ini adalah meningkatnya mutu pendidikan Matematika Sekolah Dasar di Kabupaten Takalar. Metode yang digunakan dalam pelaksanaan pelatihan ini berupa metode demonstrasi dan tanya jawab tentang teknik berhitung cepat yang dilakukan oleh guru-guru sekolah dasar Se-Kabupaten Takalar. Adapun kegiatan ini dimulai dengan observasi dan wawancara dengan kepala bidang guru dan tenaga kependidikan Dinas Pendidikan Kabupaten Takalar. Kegiatan ini dilaksanakan secara Daring Syncronouse menggunakan aplikasi meeting Zoom dikarenakan wabah Pandemi Covid – 19 masih mengganas. Peserta yang hadir saat pelaksanaan pelatihan sebanyak 33 orang. Hasil angket persepsi guru tentang penggunaan teknik berhitung cepat semua guru-guru merasa senang dengan kemampuan ini, demikian pula bahwa guru-guru akan memanfaatkan teknik ini dalam membelajarkan berhitung bagi murid-muridnya.